Ramadan fasting in patients with a stoma: A prospective study of quality of life and nutritional status - Altuntaş, Yunus Emre; Gezen, Fazlı Cem; Sahoniz, Turgut; Kement, Metin; Aydın, Halime; Şahin, Fatma; Okkabaz, Nuri; Öncel, Mustafa (H M P Communications, 2013)
Ramadan fasting is an Islamic obligation for healthy Muslims after the age of puberty. Persons with an acute or chronic disease may be excused from this obligation; the degree of the disease is an important parameter for not fasting. Little is known about the effect of fasting on persons with a stoma. A prospective study was conducted among 56 patients with a cancer-related fecal stoma (33 [58.9%] male, mean age 55.9 +/- 13.1 years) over two periods of Ramadan to analyze the effect of fasting 15 to 16 hours on nutritional and metabolic status and quality of life. Eligible patients were divided into two groups: fasting (n = 14) and nonfasting (n = 42). Demographic and stoma information, as well aS disease and treatmentrelated variables, were evaluated. Participants completed cancer patient and colorectal cancer patient quality-of-life in and rated their religious orientation. Laboratory tests (blood urea nitrogen, creatinin, cholesterol, prealbumin, albumin, and transferrin) were performed 1 to 3 weeks before Ramadan, and questionnaires and tests were repeated 1 to 3 weeks after Ramadan in people who fasted. Demographic parameters, including religious orientation scale scores, were similar between fasting and nonfasting groups. Patients in the fasting group had significantly higher albumin levels (4.6 +/- 0.2 versus 4.1 +/- 0.4, P = 0.001), prealbumin levels (27.6 +/- 7.4 versus 21.3 +/- 8.5, P = 0.018), and global health status scores (81.5 16.7 versus 68.3 +/- 20.1, P = 0.030) than patients in the nonfasting group. Patients who fasted also had their stoma for a longer period of time than patients in the nonfasting group (average 9 months [range 3-87 months] in the fasting versus 4.5 months [range 3-36 months] in the nonfasting group, P = 0.084), and the proportion of patients with a permanent stoma was higher in the fasting group than in the nonfasting group (P = 0.051). Ramadan fasting had almostno influence on quality of life. Fasting lowered prealbumin levels (27.6 +/- 7.4 versus 21.2 +/- 4.4; P = 0.046), but did not adversely affect other nutritional or global health status variables. Most patients in the fasting group (13, 92.9%) stated they would feel sad if they were not fasting. The results of this study suggest that although fasting may decrease prealbumin levels, persons with a stoma and good nutritional status may decide for themselves whether to fast.
WOS: 000330082000006
PubMed ID: 23669258
Keywords: Prospective Study; Surgical Stoma; Fasting; Islam; Nutritional Status